A study of value-based total performance towards UKM’s top management staffs by using Partial Least Square (PLS) method / Nur Aiman Hanis Hasim - Hasim, Nur Aiman Hanis (2012)
The aim of this study was to investigate the factors that contribute to organizational excellence based on core values. Respondents in this study focused on the top management staff of UKM to see how these core values practiced in the university. Lack of performance measurement using the measurement of intangible and the core values and also the absence of a relationship framework as a guide to measure the performance organizations in Malaysia have an idea to conduct this research. Method of Partial Least Square (PLS) and software SmartPLS was used in order to analyzed the survey data of 70 questionnaires that were distributed to top management of UKM, who is also a member of the Mesyuarat Ketua Bahagian (MKB) of UKM. The findings of this study have identified five different paths connecting the leadership criterion to the performance result criterion. Leadership criterion shows a strong relationship between Best Practices criterion compared to criterions Employee Focus and Culture